2003
DOI: 10.1007/s00542-003-0323-x
|View full text |Cite
|
Sign up to set email alerts
|

A design method ? based on a shock-response-spectrum analysis ? for reducing acoustic noise of a seeking control system in a hard disk drive

Abstract: A design methodology for reducing seeking noise in a hard disk drive has been developed. This method can optimize the seeking current according to a shockresponse-spectrum analysis. It was verified experimentally that this method can reduce the seeking noise by about 4 dBA on average without increasing the seeking time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…By using this index, we can estimate effect of the unobservable oscillations caused by mechanical resonances. Moreover, this study employs the shock response spectrum (SRS) analysis that handles the transient-state characteristics of mechanical resonances [Smallwood (1981); Okuyama et al (2003); Lalanne (2003)]. The results of this study are confirmed through track-seeking experiments on a HDD.…”
Section: Introductionmentioning
confidence: 88%
“…By using this index, we can estimate effect of the unobservable oscillations caused by mechanical resonances. Moreover, this study employs the shock response spectrum (SRS) analysis that handles the transient-state characteristics of mechanical resonances [Smallwood (1981); Okuyama et al (2003); Lalanne (2003)]. The results of this study are confirmed through track-seeking experiments on a HDD.…”
Section: Introductionmentioning
confidence: 88%
“…One kind of acoustic noise in HDDs is seeking noise generated by seeking operation. Seeking noise has been assumed to originate from transient vibrations, not steady vibrations, in the mechanical parts (13) . Therefore, bumpless switching is needed to reduce this noise.…”
Section: Servo System In Hard Disk Drivesmentioning
confidence: 99%
“…Theoretical approaches to the IVC have mostly appeared in the HDD community [7][8][9][10][11][12][13][14]. Design methods based on pole placement ideas [8,9] and linear-quadratic optimizations [7,8] are proposed.…”
Section: Initial Value Compensationmentioning
confidence: 99%
“…One of the acoustic-noises in an HDD is a seeking noise generated by a seeking operation. It is assumed that the seeking noise originates from transient vibrations, not steady vibrations, of the mechanical parts [13]. Therefore, bumpless switching is needed for reducing the seeking noise.…”
Section: A Servo System In Hard Disk Drivesmentioning
confidence: 99%
See 1 more Smart Citation